REKONSTRUKSI PROBLEMATIKA SOSIAL DALAM UPAYA PEMBERDAYAAN DAN PERLINDUNGAN ANAK TERLANTAR MELALUI ADOPSI - MS Udin (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2018)
One of the problems in this country is the large number of school-aged children who cannot continue schooling due to disasters and others, in large cities abandoned children with school age can easily be found alongside roads, terminals, stations and so on. Children, whatever their background is an investment in the future, every child in essence has the rights and obligations as a child in a family, but in reality there is often a neglect of the fulfillment of children's rights, this is probably due to economic conditions, family social and psychology. Child protection is a business that establishes conditions in which every child can exercise his rights and obligations. The protection of children is a manifestation of the existence of justice in a society. Thus, child protection must be sought in various fields of state and community life. Child protection is a field of national development. Protecting children is protecting people is building whole people